Bibliometric, theoretical, and conceptual analysis on the study of governance in the university field, period 2018-2022 - Gutiérrez-Durán , José Eduardo (2025)
Introduction: This article is part of a doctoral research project based on theoretical and conceptual foundations on the topic of university governance.Objective: The main objective of this research was to develop a bibliometric, theoretical, and conceptual analysis that provides a comprehensive overview of the study of university governance during the period 2018–2022.Method: A qualitative approach was used, with descriptive analysis.Results: The research produced a theoretical and conceptual framework on university governance, as well as two visualization maps generated using VosViewer software: Map 1: Countries where scientific studies and academic articles on university governance have been developed (during the study period); Map 2: Most prevalent topics and terms in scientific studies and academic articles on university governance (during the study period). The two products obtained (theoretical and conceptual framework, as well as the visualization maps generated by the bibliometric review) provide an overview of academic research on the topic of governance in the university setting.Conclusion: There is a robust theoretical and conceptual framework for the study of governance in the university setting. Following the bibliometric analysis and the creation of the visualization maps derived from the analysis, a high concentration of scientific studies and academic articles on university governance was identified, primarily in North America (United States and Canada) and Europe (England, Germany, Italy, France, Spain, Portugal, among others). Likewise, the main themes and predominant terms in scientific and academic production on governance in the university setting were identified, including university administration, comparative studies, governance, universities, COVID-19 pandemic, globalization, entrepreneurship, university policies, educational accreditation, technology, among others.